Impact of long run investment of stock in developed & developing economies - Muhammad Jawad; Munazza Naz; Sohail Rizwan; Zaib Maroof; Nauman Waheed; Afkar Majeed; Tahani Rashid (Cogent Economics & Finance, 2022)
The current investigation explained the dissemination of long-term share yields grounded on the historic record of share marketplace outcome in an extensive cross section of 39 developing and developed nations in time span from 1841 to 2021. Our wide-ranging data set sample mitigates apprehensions over survivor and informal data biases that outbreak other work in this range. A bootstrap simulation analysis suggests considerable ambiguity about long-horizon share market effects, and we approximate a 12% probability that a diversified stockholder with a 30-year venture time horizon will lose comparative to inflation. The findings oppose the predictable guidance that shares are safe investment avenue over long holding time periods.
Keywords: 330; Stock; long run; developed and developing economies; investment